Using chlorophyllic organic matter degradation in the deep St. Lawrence Estuary as an indicator of water column remineralization - Lévesque, David; Lebeuf, Michel; Starr, Michel (Frontiers in Marine Science, 2024)
Coastal hypoxia, driven by remineralization of chlorophyllic particulate organic matter (POM) in dark environments, poses a threat to deep estuarine and shelf ecosystems. To better understand the fate of POM along a depth gradient, we investigated the degradation of chloropigments, particulate organic carbon (POC), and nitrogen (PON) across the water column in the St. Lawrence Estuary, one of the largest and deepest estuarine system in the world that is facing strong persistent and increasing hypoxia. Our objectives were to establish causal relationships among suspended POM descriptors and assess the potential of a chlorophyll-based degradation index, known as the chlorin index (CI), in evaluating OM degradation within the water column. The CI, ranging from 0.2 for pure chlorophyll to almost 1 for highly degraded pigments, was initially developed for uses in the sediments. Water samples from multiple depths were collected, characterized, and statistically analyzed with a combination of variation partitioning, non-linear regressions and piecewise structural equation modeling (pSEM).We found that the combined influence of chloropigments and depth explained 84.0% of POC and 90.0 % of PON variations; the pure fraction attributed to chloropigments accounted for 73.4% and 75.6% (R 2 adj, both with p < 0.001), respectively. The decline of chloropigments, PON, and POC with increasing depth was reflected by the concomitant increase in CI, whose rate decreases as particles sink resulting in reduced degradation due to less labile organic matter. The pSEM causal model indicated that CI increased with depth and POC concentration, while it decreased in the presence of elevated PON concentrations, known for their high reactivity. The direct effect of depth on CI could be linked to the distinct water column properties influencing particle residence time and thus the degradation potential by biotic and abiotic factors. Finally, CI explained 86% (R 2 ) of the apparent oxygen utilization highlighting the strong connection between POM degradation and hypoxia of deep coastal ecosystems. Our study underscores the utility of the chlorin index as a simple yet robust tool for monitoring OM degradation in the water column, particularly in the St. Lawrence Estuary.